Correlation between Neutrophil Counts and Salmonella IgM in Typhoid Fever Patients at Emanuel Hospital Banjarnegara - Haryanti, Anik; Nugroho, Yusuf Eko; Faizal, Imam Agus (Asosiasi Institusi Pendidikan Tinggi Teknologi Laboratorium Medik Indonesia, 2025)
Background: Typhoid fever is an infectious disease caused by Salmonella typhi and remains a significant public health problem in endemic regions. The incidence continues to rise annually, particularly among children. During infection, the immune system responds through both hematological and serological mechanisms, including increased neutrophil counts and the production of Immunoglobulin M (IgM). Neutrophils act as the first line of defense against bacterial invasion, while IgM is the earliest antibody produced during acute infection. Although many studies have independently examined hematological and serological parameters in bacterial infections, limited research has explored the relationship between neutrophil counts and Salmonella IgM in pediatric typhoid fever, especially in endemic areas such as Banjarnegara, Indonesia. Objectives: This study aims to analyze the relationship between neutrophil counts and Salmonella IgM results in pediatric patients with typhoid fever. Materials and Methods: This study is a cross-sectional design utilizing secondary data obtained from the Electronic Medical Records (EMR) and Laboratory Information System (LIS). Results: The results showed that 18 patients (47.4%) had normal or high neutrophil counts, while 2 patients (5.3%) had low neutrophil counts. Regarding Salmonella IgM results, 5 patients (13.2%) tested negative, whereas 33 patients (86.8%) tested positive. Conclusions: The Spearman statistical test yielded a p-value of 0.002 (p < 0.05) with a correlation coefficient of 0.480, indicating a significant relationship between neutrophil counts and Salmonella IgM results at Emanuel Hospital, Banjarnegara. The correlation between neutrophil counts and Salmonella IgM results is considered moderate.